KINERJA PASAR MODAL NEGARA – NEGARA BERKEMBANG DI ASIA PASIFIK SEBELUM DAN SELAMA PANDEMI COVID 19 - Kosim, Belliwati; Maulani, Sri Rizki (Universitas Muhammadiyah Palembang, 2021)
Purpose–The purpose of this study was to determine whether there were any differences in capital market performance in developing countries in Asia Pasific before and during the covid 19 pandemicDesign/methodology–The research design used in this study is a quantitative method with a descriptive and comparative research method, namely to determine whether to know the effect between two or more variables. The data analysis methods used to answer the hypothesis used data normality and Paired Sample t Test.Findings -Based on the test results (Paired Sample t Test) showed that there were differences in capital market performance in developing countries in Asia Pacific before and during the Covid 19 pandemic